Pengaruh Keadilan, Kebijakan Pimpinan Dan Pemberian Motivasi Terhadap Semangat Kerja Pegawai Rumah Sakit Daerah - Surya Dikadarma Sitorus; Riska Tampubolon; Riris Dermawaty. S; Risfan Riadi Rambe; Mhd. Suhail; M. Ridha Tarigan (Journal of Trends Economics and Accounting Research, 2022)
The formulation of the problem in this study is whether justice, leadership policies and giving motivation are positive and simultaneous on the morale of the employees of the Regional General Hospital DR. Tengku Mansyur Tanjungbalai City. This study aims to determine the effect of justice, leadership policies and providing motivation on the morale of the employees of the Regional General Hospital DR. Tengku Mansyur Tanjungbalai City. The sample in this study were all employees of the Regional General Hospital DR. Tengku Mansyur Tanjungbalai City, amounting to 33. The data analysis technique in this study was Multiple Linear Regression. The results of this study indicate, partial justice has a positive and significant effect on employee morale; The leadership policy partially has a positive and significant effect on employee morale; Motivation partially has a positive and significant effect on employee morale; Justice, leadership policies and motivation simultaneously have a positive and significant effect on employee morale.